The HIV Protein gp120 Alters Mitochondrial Dynamics in Neurons - Avdoshina, Valeria; Fields, Jerel Adam; Castellano, Paul; Dedoni, Simona; Palchik, Guillermo; Trejo, Margarita; Adame, Anthony; Rockenstein, Edward; Eugenin, Eliseo; Masliah, Eliezer; Mocchetti, Italo (Neurotoxicity research, 2016)
Neurotoxicity of human immunodeficiency virus-1 (HIV) includes synaptic simplification and neuronal apoptosis. However, the mechanisms of HIV-associated neurotoxicity remain unclear, thus precluding an effective treatment of the neurological complications. The present study was undertaken to characterize novel mechanisms of HIV neurotoxicity that may explain how HIV subjects develop neuronal degeneration. Several neurodegenerative disorders are characterized by mitochondrial dysfunction; therefore, we hypothesized that HIV promotes mitochondrial damage. We first analyzed brains from HIV encephalitis (HIVE) by electron microscopy. Several sections of HIVE subjects contained enlarged and damaged mitochondria compared to brains from HIV subjects with no neurological complications. Similar pathologies were observed in mice overexpressing the HIV protein gp120, suggesting that this viral protein may be responsible for mitochondrial pathology found in HIVE. To gain more information about the cellular mechanisms of gp120 neurotoxicity, we exposed rat cortical neurons to gp120 and we determined cellular oxygen consumption rate, mitochondrial distribution, and trafficking. Our data show that gp120 evokes impairment in mitochondrial function and distribution. These data suggest that one of the mechanisms of HIV neurotoxicity includes altered mitochondrial dynamics in neurons.